2020
DOI: 10.1007/s42154-019-00086-w
|View full text |Cite
|
Sign up to set email alerts
|

Personality Openness Predicts Driver Trust in Automated Driving

Abstract: Maintaining an appropriate level of trust in automated driving (AD) is critical to safe driving. However, few studies have explored factors affecting trust in AD in general, and no study, as far as is known, has directly investigated whether driver personality influences driver trust in an AD system. The current study investigates the relation between driver personality and driver trust in AD, focusing on Level 2 AD. Participants were required to perform a period of AD in a driving simulator, during which thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…On one hand, several studies investigated trust regarding specific AI-technologies. Li et al ( 2020 ) consistently observed correlations between openness and trust in automated driving. While the participants showed lower trust in automated driving with higher openness in a questionnaire, they also showed a higher monitoring frequency, more frequent, and earlier and longer “take overs” in an automated driving simulator.…”
Section: Outlook On Distributed Cognition In An Ai-enhanced Futurementioning
confidence: 94%
See 1 more Smart Citation
“…On one hand, several studies investigated trust regarding specific AI-technologies. Li et al ( 2020 ) consistently observed correlations between openness and trust in automated driving. While the participants showed lower trust in automated driving with higher openness in a questionnaire, they also showed a higher monitoring frequency, more frequent, and earlier and longer “take overs” in an automated driving simulator.…”
Section: Outlook On Distributed Cognition In An Ai-enhanced Futurementioning
confidence: 94%
“…Individuals high in openness might strive for more intellectually demanding tasks and thus do not heavily rely on automated systems (but see Zhang et al, 2020 , for conflicting results). Additionally, higher extraversion was related to less trust in the questionnaire but no other effects were observed (Li et al, 2020 ). In contrast, Kraus et al ( 2021 ) did not observe a relationship between openness and trust in automated driving, but indirect effects of neuroticism, extraversion, and agreeableness.…”
Section: Outlook On Distributed Cognition In An Ai-enhanced Futurementioning
confidence: 99%
“…This is typically time-variant, and it can be influenced by the stress, workload, cognition, scenario, and personality of the driver [214,215]; even the educational background and usage experiences can be associated with trust [216,217]. Li et al [218], for example, investigated the relationship between driver personality and driver trust in the AV and discovered a significant correlation between Openness and driver trust. Xing et al [74] summarized all influential factors into three categories: prior, short-term, and long-term factors.…”
Section: F Monitoring Of Driver Trust On Vehicle Automationmentioning
confidence: 99%
“…Intelligent agents are now part of our lives and their numbers are expected to increase [ 1 , 2 , 3 ]. Therefore, the smartness, safety, and efficiency of interactions and collaborations between humans and agents should continue to improve [ 4 , 5 , 6 , 7 , 8 , 9 ]. In particular, autonomous driving technology could allow humans to share control with intelligent vehicles [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%